Despair in youth: an analysis by gender - Valdez Medina, José Luis (2014)
Despair generates personal devaluation, which can lead to states of greaterdepression. The aim was to describe experiences of despair in a sample of 224 Mexican youths of both genders aged 26 on average. A questionnaire of nine reagents validated by expert judges was used. The results show that women have experienced it more frequently. Lack of hope in participants is evidenced in the following areas: academic, occupational, economic, emotional, personal, accident / illness. With regard to the causes, women attribute it to internal factors whilemen to external factors. The results reveal that livingin despair increases the risk of losing stability and health in general.